Playing the game: re-creational careers, a qualitative study of working lives in context - Amal El-Sawad (2002)
In an attempt to make sense of the concept of career this thesis reports findings from a case-study of twenty graduate level employees within one organisation. Responding to the problematic features of career studies to date, a cross-disciplinary, critical, interpretive, qualitative, contextualised study of career is presented which rejects the dichotomous stances characterising much existing literature and instead embraces the dialectal nature and ontological duality of career. Thus attention is devoted to both the organisation and individual, structure and agency as well as stasis and adaptation. The study is situated in its historical, cultural and social context and the research agenda is purposefully emergent allowing those being studied to lead the way to the key dimensions of career. [Continues.]